Capacity building for environmental law in the Asian and Pacific region : (Asian Development Bank Cop., 2002)
The emphasis of this book is on environmental law capacity building through educational and institutional development to enable as many people as possible to address current problems and develop laws for the aspiration of sustainable development. It includes international regional, national and local dimensions of environmental law. Key principles include the right to environmental quality, the obligation not to cause environmental harm, the precautionary principle, the common heritage of human kind, and other pertinent topics.